Does Urban Agriculture Have a Positive Impact on Food Security? (The Case Study of Tehran City) - Farzam, Mahrooz; Najafabadi, Maryam Omidi; Lashgarara, Farhad; Hosseini, Seyed Jamal Farajollah (Journal of Environmental Accounting and Management, 2026)
In order to achieve food security, various factors such as food safety as well as healthy and nutritious diet are the main core values of human health development in all societies across the world. One important strategy to achieve this goal is urban agriculture (UA). Therefore, the main purpose of this study was to investigate the role of UA in improving food security and safety. This research had an applied and quantitative nature in which the questionnaire was used as the research instrument. The statistical population included all residents (n=574) of the Tehran city in Iran, who had attended the courses focused on agricultural and extension education, held in plant clinics by observers and experts in all agriculture and natural resources’ areas of each districtduring a three-month period (October, November, and December) of 2019. To determine the sample size, the Cochran formula was applied and a total number of 161 samples were selected using the simple random sampling method. In general, the study results demonstrated the positive and significant effect of UA functions on the food security. In this regard, environmental (0.807), economic (0.730), and social (0.192) functions were respectively distinguished as the most important factors shaping the food security. Moreover, the results revealed that the impact of environmental, economic and social functions of the UA on the food security were statistically significant at the level of 99%; while, the UA physical-mental function’ effect on the food security was statistically meaningful at the level of 95%. Based on mentioned findings, in order for agricultural development and extension services to succeed in urban area, special place should be dedicated to UA and sufficient funding and facilities must be allocated by the government for the citizens who are willing to work in agriculture related fields and this should be seriously considered by the policy makers and authorities in the ministry of Agricultural-Jihad.